Low loss polypropylene-silicon composites for millimetre wave applications. (August 2018) - Krupka, J.; Shakhil, P.G.; Arun, N.S.; Ratheesh, R.; Jantunen, H.; Kim, H.T.; Sebastian, M.T.
Graphical abstract: Highlights: Developed polypropylene-silicon composite. The composite shows a decrease in loss tangent with increasing frequency. The composite is useful for high frequency applications such as Internet of Things and 5th Generation wireless communication. Abstract: Polypropylene-silicon composite laminates were fabricated via hot pressing and their dielectric properties up to 35 GHz were studied. The loss tangent was found to decrease with increasing frequency whereas an increasing trend of loss tangent has previously been reported in the literature for such composites. The decreasing trend of the loss tangent with frequency is due to the decreasing conductor loss of silicon (Si) and indicates the possibility for use in high frequency applications such as the Internet Of Things and 5 t h generation wireless communication. The composite containing 25 vol% of Si had a relative permittivity of 3.5 and a loss tangent of 0.001 at 35 GHz. The coefficient of thermal expansion and the thermal conductivity of 40 vol% Si loaded composites were 51 ppm/ o C and 2.23 W/mK, respectively. The thermal conductivity of the composite increased by 163% and 913% for 25 and 40 vol% Si addition, respectively.